ANALISIS PEMBELAJARAN FISIKA KELAS X SMA NEGERI DI KOTA CIREBON BERDASARKAN LITERASI SAINS - Rohman, Saeful; Rusilowati, Ani; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2017)
Science and technology has a significant role to increase human kinds prosperity. The ability to comprehend science and technology literature is a requirement for us to apply science and technology on the right way for the sake of humans prosperity and safety. The International research result showed that Indonesian students low ability of literacy. The students ability of scientific literacy is influenced by teachers competence in delivering materials that use scientific literacys aspects. This reseach aimed at analyzing the teachers ability of scientific literacy on learning materials and the learning process in their class and the students ability of scientific literacy as result of the learning process. This research used qualitative approach with the research subject of 12 teachers in grade X and 325 students of grade X from 9 state senior shcool at Cirebon. The analysis of scientific literacy used was conducted through test, non-test, and documentation. Generally, result of research indicated the teachers ability of scientific literacy was high, the emergence of scientific literacy was medium, and the students ability of scientific literacy after the learning process was medium. Based on the result of research, it can be concluded that the upgrading quality of teaching process in the class, in which the ability of scientific literacy appear is extremely needed to increase the students ability of scientific literacy